IMPROVING STUDENTS’ WRITING ABILITY IN SHORT MESSAGE THROUGH PJBL STRATEGY (A Classroom Action Research at 8th Grade Students of SMPN 43 Surabaya): English - Muhamad Saiful Anam; Lusy Tunik Muharlisiani; Erna Sulistyawati (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
Writing is one of skills which is difficult to master. In teaching writing, a teacher must be capable of employing strategies that engage students and motivate them in the learning process. One such strategy is Project Based Learning (PjBL), which aims to make the teaching of writing easier and more interesting. This study utilized a classroom action research design and involved 31 students from VIII F of SMPN 43 Surabaya. It was conducted in two cycles, each consisting of two meetings, and followed four steps: planning, implementation, observation, and reflection. After each cycle, an evaluation test was administered to assess the students' improvement in writing short messages. The research utilized test data collection, interviews with the English teacher and students, and an observation sheet as research instruments. The findings demonstrated that the implementation of the Project Based Learning (PjBL) strategy effectively enhanced the students' ability to write short messages, as evidenced by an improvement in the average test scores. In the preliminary test, 7 students (22.58%) met the success criteria, while in the first cycle, 22 students (70.96%) achieved success. By the second cycle, 28 students (90.32%) met the success criteria. Factors such as the teacher's explanation in the classroom and the students' attention, participation, and interest played a significant role in improving the students' writing ability. Consequently, the Project Based Learning strategy is recommended as an alternative approach for English teachers to enhance students' writing skills. Furthermore, future researchers can use this study as a reference for conducting further research on improving writing abilities.